KETERSEDIAAN BERAS DAN AKSES PANGAN DALAM KAJIAN KETAHANAN PANGAN DI KABUPATEN GUNUNGKIDUL TAHUN 2013 - , WAWAN ARIJAL, Umi Listyaningsih S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research are (1) Determine the availability of rice as a source of calories in the population by sub district of Gunungkidul. (2) Determine the food access of population by sub districts in Gunungkidul. (3) Determine food security based on the availability of rice and food access by sub districts in Gunungkidul. (4) Determine the spatial pattern of food security by districts in Gunungkidul. The method used is the analysis of secondary data with data source Gunungkidul Yearbook 2012 and Household Profile Poverty Reduction Targets in Yogyakarta 2012. Data processing was performed by using the method of Food Security and Vulnerability Atlas or FSVA with specialized the availability of rice to represent the dimensions of food availability. The discussion of the results of calculations performed by descriptive with reference to the determination of each level determinants of food security indicators and composite results are presented in maps to analyze the spatial pattern The results showed there are 5 districts with the availability of highly resistant rice categories are Semin, Ngawen, Gedangsari, Patuk and Ponjong , 8 districts with resistant categories, 4 districts with quite resistant category and 1 district with vulnerable category namely Wonosari. There are 3 districts with quite resistant categories of food access are Wonosari, Semanu and Rongkop , 12 districts with rather vulnerable categories, 3 district with vulnerable categories namely Gedangsari, Ngawen and Saptosari. The results analysis of composite food security shows 4 districts in Gunungkidul including the quite resistant of food category namely Patuk, Semin, Ponjong and Rongkop, 1 districts with vulnerable category of food there is Wonosari, 13 others districts are including rather vulnerable of food categories. Spatial patterns of food security of district with quite resistant categories clustered in the eastern region, kinda Vulnerable category of food spread almost in all regions and ditrict with vulnerable category of food is in the middle of Gunungkidul region. The spatial pattern is influenced by the physical geographic condition and socio-economic characteristics of the population.